Вербалізація лексичного регулятиву Німеччина в епістолярних текстах Лесі Українки - Богдан, Світлана; Bohdan, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто особливості функціонування лексичного регулятиву Німеччина як домінувального елемента в системі етнічних стереотипів епістолярних текстів Лесі Українки; акцентовано увагу на системі словесних засобів актуалізації номінативного поля, що формують його; виокремлено ядерні та периферійні одиниці, які створюють її особистісний образ Німеччини, а також проаналізовано їх синтагматику; встановлено чинники, що вплинули на певні модифікації у творенні цього гетеростереотипу на противагу типологічному для українців. The article describes the functioning peculiarities of the regulative Nimetchyna/Germany as a dominant element in the system of the ethnic stereotypes of Lesia Ukrainka's epistolary texts. In the focus of attention are the issues of verbal explication of the nominative field of the lexical means, which form it. Nuclear and peripheral units, which form the personality image of Germany, have been highlighted. It has been revealed that the major epistolary nominations include those derived from the core lexeme Nimechchyna – nimec`kyj / -e, -a, po-nimec`ky, nimka, nimci, nimchenyata, nimota and toponymic names, such as Berlin and its derivative berlіnsky / -s, -e. The emphasis is laid on the analysis of their syntagmatic and semantic potential in the text actualization, and on the factors affecting some modifications in the formation of this heterostereotype. Special attention is paid to their distinctive features as compared to the typological for the Ukrainians’ perception of them.
The Verbalization of the Regulative 'Nimetchyna/Germany' in Lesia Ukrainka`s Epistolary Texts
Keywords: регулятив; епістолярний текст; етнічні стереотипи; гетеростереотип; номінативне поле; regulative; epistolary text; ethnic stereotypes; heterostereotype; nominative field